Gluteal lymphoedema associated with lower extremity lymphoedema: A preliminary study with indocyanine green lymphography and magnetic resonance imaging. (January 2023) - Karlsson, T.; Mackie, H.; Ho-Shon, K.; Blackwell, R.; Heydon-White, A.; Koelmeyer, L.; Suami, H.
Summary: Introduction: Indocyanine green (ICG) lymphography studies have identified that one in three to five patients with cancer-related lower extremity lymphoedema (LEL) demonstrated dermal backflow extending to the gluteal region. This study aimed to further characterize gluteal lymphoedema using contemporaneous magnetic resonance imaging (MRI). Patients and methods: Twenty-eight patients with unilateral advanced LEL who underwent both ICG lymphography and MRI prior to any surgical procedure were included in this study. The patients were divided into two groups with/without gluteal lymphoedema by the presence of dermal backflow on ICG lymphography. MRI was used to evaluate tissue changes. Results: Ten patients demonstrated gluteal lymphoedema on ICG lymphography and had a higher incidence of skin hypertrophy in the gluteal region. However, no difference in excess leg volume was found between the two groups. A trend of increasing gluteal subcutaneous tissue in the affected side was identified in patients with gluteal lymphoedema with a median increase of 20% compared with an 11% increase in the non-gluteal lymphoedema group. The excess gluteal subcutaneous tissue was positively correlated to ipsilateral excess leg volume. Conclusion: The gluteal lymphoedema group on ICG lymphography had skin thickening in the gluteal region and was likely identified in the secondary cancer-related group. Surgical and conservative management options for gluteal lymphoedema need to be considered in advanced LEL.